2D layered group IIIA metal chalcogenides: synthesis, properties and applications in electronics and optoelectronics. Issue 22 (2nd December 2015) - Huang, Wenjuan; Gan, Lin; Li, Huiqiao; Ma, Ying; Zhai, Tianyou
Abstract : Two-dimensional group IIIA metal chalcogenides have promising potential in applications such as nano-electronics and optoelectronics as well as flexible devices. Abstract : The remarkable properties of graphene have inspired great research interest in two-dimensional layered materials (2DLMs) with novel electronic and optical attributes. As a class of graphene-like 2DLMs, ultrathin group IIIA metal chalcogenides (GIIIAMCs, metal = In, Ga; chalcogen = S, Se, Te) have shown great potential in electronics and optoelectronics. In this review, we first introduce the crystal structures and their unique advantages in specific potential applications. Then, we summarize the progress in the fabrication of GIIIAMCs in the framework of top-down and bottom-up methods. Next, their recent achievements regarding enhanced field-effect transistor and photodetector applications are discussed in detail. In addition, the construction strategies of hybrid GIIIAMCs heterostructures and their applications in electronics and optoelectronics are presented. Finally, this review is concluded with some perspectives and an outlook for continued research.